Landscapes in transition - Finlayson, Bill; Warren, Graeme (Levant supplementary series ;, 2010)
This volume presents papers focusing on archaeological approaches to landscape in the context of the adoption of agriculture in Southwest Asia and Northwest Europe. Case studies are presented from these contrasting regions.